2001
DOI: 10.1038/sj.cdd.4400792
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide generation occurring during 7β-hydroxycholesterol- and 7-ketocholesterol-induced apoptosis is caspase independent and is not required to trigger cell death

Abstract: Biological activities of oxysterols seem tightly regulated. Therefore, the ability to induce cell death of structurally related oxysterols, such as those oxidized at C7(7a-, 7b-hydroxycholesterol, and 7-ketocholesterol), was investigated on U937 cells at different times of treatment in a concentration range of 5 ± 80 mg/ml. Whereas all oxysterols accumulate inside the cells, strong inhibition of cell growth and increased permeability to propidium iodide were observed only with 7b-hydroxycholesterol and 7-ketoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 96 publications
(106 reference statements)
6
44
1
Order By: Relevance
“…However, DNA fragmentation was similarly enhanced in cells treated with both hydroxysterols. By using the broad-spectrum caspase inhibitor Z-VAD.fmk, 31,46,47 we demonstrated that caspases activation plays an important role in the antiproliferative effect initiated by 7b-OHsito. This was not the case for cells treated with 7b-OHchol, which were not affected by the caspase inhibitor.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, DNA fragmentation was similarly enhanced in cells treated with both hydroxysterols. By using the broad-spectrum caspase inhibitor Z-VAD.fmk, 31,46,47 we demonstrated that caspases activation plays an important role in the antiproliferative effect initiated by 7b-OHsito. This was not the case for cells treated with 7b-OHchol, which were not affected by the caspase inhibitor.…”
Section: Discussionmentioning
confidence: 92%
“…23 In the presence of the pancaspase inhibitor, Z-VAD.fmk, apoptotic events were not completely suppressed. 31 Hence, 7b-OHsito may trigger apoptosis through postmitochondrial caspase cascades and DNA fragmentation. 48,49 In contrast, 7b-OHchol showed no effect on cell cycle and induced cell death mechanisms leading to DNA fragmentation that were not delayed by the inhibitor Z-VAD.fmk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in other instances where induction of apoptosis is accompanied by an elevation of ceramide, FB 1 failed to prevent the apoptotic response while blocking ceramide production (Nagy et al, 2000;Miguet et al, 2001).…”
mentioning
confidence: 97%
“…The lipid contents of cholesterol (esterified and unesterified), phosphatidylcholine, and sphingomyelin were determined. To this end, lipids were extracted and analyzed by capillary gas chromatography and mass spectrometry (CGC/MS) as previously described (33).…”
Section: Effects Of Caspase Inhibitors On Nile Red Fluorescence Patternmentioning
confidence: 99%